Pengujian Interoperabilitas pada IoT Middleware dalam Mengatasi Permasalahan Interoperabilitas - Ulul Albab Khatami; Eko Sakti Pramukantoro; Fariz Andri Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Internet of Things (IoT) plays an important role in the development of the Internet today and in the future. Along with the large number and types of devices that are connected, a problem arises called interoperability. Interoperability problems in IoT can be divided into 3 categories which are network interoperability, semantic interoperability, and syntactical interoperability. Recent development of IoT middleware has lead to resolve of interoperability problems in steps. This research has conducted a test on IoT middleware. The test was done to answer the question of whether IoT middleware has the ability to resolve interoperability problems if a system is run together. The Interoperability test uses a model called interoperability assessment methodology. The model has 9 parameters which are commonly used based on the researcher's needs. The results of the interoperability show the level of success of sending data from each node sensor to the middleware. Results gained has shown that the Wi-Fi protocol has a 96,67% rate, the 6LoWPAN protocol having 96,11% rate, and the BLE protocol having a 100% rate. For the interoperability test conducted using the interoperability assessment methodology model, it can be concluded that IoT middleware can resolve network, semantic, and syntactical interoperability problems simultaneously. The performance test showed that CPU usage was in the 0%-23% range during 3 hours, which was how long the test was conducted. Currently, the memory utilized when the system was run simultaneously was 29 MB - 40 MB.